2003
DOI: 10.1002/mrdd.10068
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic causes of hearing loss

Abstract: Nongenetic as well as genetic etiologies must be explored in the child with identified hearing loss. Graduates of the neonatal intensive care unit are at increased risk for developing hearing loss due to hypoxia, hyperbilirubinemia, very low birth weight, and ototoxic medications. Although meningitis has decreased in frequency, it is still a risk factor for hearing loss. Cytomegalovirus remains the most common congenital infection and a relatively common etiology of hearing loss, which can be progressive. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 87 publications
1
34
0
3
Order By: Relevance
“…No entanto, na análise múltipla, na qual tentamos eliminar a ação conjunta de outros vários fatores, não se manteve 17,26 .…”
Section: Discussionunclassified
“…No entanto, na análise múltipla, na qual tentamos eliminar a ação conjunta de outros vários fatores, não se manteve 17,26 .…”
Section: Discussionunclassified
“…However, in the multiple analysis, in which we attempted to eliminate the joint action of various other factors, this association was not maintained. 17,26 As regards hyperbilirubinemia, the data in the literature point it out as an important cause of deafness. 27 In the present study assessment, it was not identified as a risk factor in the bivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Risk indicators that are marked with a section symbol in Appendix 2 are of greater concern for delayed-onset hearing loss. Early and more frequent assessment may be indicated for children with CMV infection, 118,125,126 syndromes associated with progressive hearing loss, 72 neurodegenerative disorders, 72 trauma, [127][128][129] or culturepositive postnatal infections associated with sensorineural hearing loss 130,131 ; for children who have received ECMO 64 or chemotherapy 132 ; and when there is caregiver concern or a family history of hearing loss. 16 For all infants with and without risk indicators for hearing loss, developmental milestones, hearing skills, and parent concerns about hearing, speech, and language skills should be monitored during routine medical care consistent with the AAP periodicity schedule.…”
Section: Communication Assessment and Interventionmentioning
confidence: 99%